Geochronology and geochemistry of Devonian magmatism in the Frontal cordillera (Argentina): geodynamic implications for the pre-Andean SW Gondwana margin. Issue 2 (19th January 2022) - Dahlquist, Juan A.; Morales Cámera, Matías M.; Alasino, Pablo H.; Tickyj, Hugo; Basei, Miguel A.S.; Galindo, Carmen; Moreno, Juan A.; Rocher, Sebastián
ABSTRACT: Whereas north of 33°S Devonian calcalkaline magmatism is notably absent, a Devonian arc is well developed to the south of 33°S. The Carrizalito, Pampa de los Avestruces, and Papagayos plutons are located in the Frontal Cordillera between 34° and 35°S. U-Pb zircon SHRIMP and LA-MC-ICP-MS data from the plutons yield Early Devonian ages of 389 ± 3 and 409 ± 3 for Carrizalito, 413 ± 2 Ma for Pampa de los Avestruces, and 346 ± 3, 393 ± 5 and 412 ± 3 Ma for Papagayos. The younger zircon age from the Papagayos pluton suggests that the Devo nian magmatism continued during the Early Carboniferous. Carrizalito and Pampa de los Avestruces plutons display metaluminous to slightly peraluminous granodiorite composition, with SiO2 ranging from 65.1 to 67.8 wt.% and from 67.9 to 69.7 wt.%, respectively, and define a magnesian calc-alkalic trend. The Papagayos pluton is metaluminous to slightly peraluminous and slightly more evolved in composition (felsic granodiorite to monzogranite), with a SiO2 content that varies between 68.4 to 70.5 wt.%, defining a magnesian with ferroan enrichment and calc-alkalic to alkali-calcic trend. These geochemical characteristics are similar to those reported for the Carboniferous arc granitoids in the Frontal Cordillera and Western Sierras Pampeanas at 27°–30°S and the archetypical calc-alkaline granitoids of the Peruvian Coastal batholith, indicating an Early Devonian magmatic arc. Rare earth element patterns ([La/Yb]N  = 10–20) with mostly slight to moderate negative Eu anomalies (Eu/Eu* = 0.62–0.80) and geochemical 'spider-diagrams' are similar to arc granitoids. Combined whole-rock Nd and Sr isotope data from the largest Carrizalito and Pampa de los Avestruces plutons (εNdt  = −4.3 and −4.6; 87 Sr/ 86 Srt  = 0.70704 and 0.70762; TDM  = ca. 1.5 Ga) together with in situ U–Pb and Hf isotope data from magmatic zircon (εHft ranging from −16.5 to −5.4; TDM  = ca. 1.7 Ga), suggest a common older continental lithosphere source. The presented data indicate tectonic segmentation in the pre-Andean margin controlling the presence or absence of Devonian subduction-related magmatism. This segmentation is best explained by changes in the tectonic plate configuration occurred in a long-lived convergent margin.